2023
DOI: 10.1021/acsanm.3c01535
|View full text |Cite
|
Sign up to set email alerts
|

Rh Nanoparticles Dispersed on ZrO2–CeO2 Migrate to Al2O3 Supports to Mitigate Thermal Deactivation via Encapsulation

Abstract: Full-scale monolithic three-way catalysts (TWCs) comprising Rh, oxygen-scavenging ZrO2–CeO2 (ZC), and γ-Al2O3 as a binder component were studied after real engine aging. The fatal irreversible deactivation that occurred under stoichiometric-lean-rich perturbation at 1000 °C for 40 h (SLR aging) was attributed to the complete encapsulation of Rh nanoparticles by ZC, leading to the physical blockage of gas adsorption. Preaging the catalyst under a rich condition at 1000 °C for 40 h (R aging) drastically mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In the thermally aged Pd catalysts (Pd/CZA, Pd/CZ, and Pd/A), the Pd particle sizes calculated from the CO chemisorption amount ( d CO ) are close to those observed by electron microscopy ( d EM ). The difference between the deactivation mechanisms of the present Pd/CZA and the previous Rh/ZrO 2 –CeO 2 could be rationalized by the larger metal loading (2 wt % Pd versus 0.8 wt % Rh) and the presence of abundant Al 2 O 3 , which play a positive role in preventing the encapsulation …”
Section: Resultsmentioning
confidence: 69%
“…In the thermally aged Pd catalysts (Pd/CZA, Pd/CZ, and Pd/A), the Pd particle sizes calculated from the CO chemisorption amount ( d CO ) are close to those observed by electron microscopy ( d EM ). The difference between the deactivation mechanisms of the present Pd/CZA and the previous Rh/ZrO 2 –CeO 2 could be rationalized by the larger metal loading (2 wt % Pd versus 0.8 wt % Rh) and the presence of abundant Al 2 O 3 , which play a positive role in preventing the encapsulation …”
Section: Resultsmentioning
confidence: 69%
“…They also found that pre‐aging the catalysts with cerium‐zirconium solid solution and alumina as supports under fuel‐rich conditions at 1000°C can greatly alleviate this deactivation mode (Figure 11b). [85] R aging promotes Rh nanoparticle migration from the ZC support to the alumina boundary. Due to the interaction with the alumina strong interaction, Rh particles are trapped near the boundary and these Rh nanoparticles are not easily and completely covered by ZC even under SLR conditions.…”
Section: Mechanism and Species Behavior During Three‐way Reactionmentioning
confidence: 99%
“…Copyright 2023, The American Chemical Society. (b) Schematic diagram of possible changes in the supported Rh nanoparticles [85] . Reproduced with permission [85] .…”
Section: Mechanism and Species Behavior During Three‐way Reactionmentioning
confidence: 99%
See 2 more Smart Citations